Distinctly Diverse PLQY and Inverse Solid‐State Luminescent Properties in Structure‐Similar Diphenyl Sulfone TADF Molecules: A Role of C─C. Issue 7 (5th June 2020) - Shi, Yu‐Hao; Wang, Fei; Sui, Ming‐Yue; Sun, Guang‐Yan; Xie, Yu‐Zhong
Abstract: Thermally activated delayed fluorescence (TADF) materials can greatly increase internal quantum efficiencies (IQEs) of organic light‐emitting diodes (OLEDs) beyond the spin statistical bottleneck of 25%. However, the mechanisms behind TADF and solid‐state luminescence are not clear. Recently, two diphenyl sulfone TADF molecules with quite similar structures, A1‐D1 and A2‐D1, have been observed to demonstrate distinctly diverse photoluminescence quantum yield (PLQY) and inverse solid‐state luminescent properties. In order to understand the origin of this phenomenon, the TADF mechanism of both molecules is studied using density function theory. The results show that strong spin–orbit coupling, low minimum energy cross point, dense triplet energy level distribution, and a mediate locally excited triplet state ( 3 LE) can facilitate the rapidly reverse intersystem crossing (RISC) process in A1‐D1 . Moreover, the solid states of both molecules are characterized via the combined quantum mechanics and molecular mechanics (QM/MM) method. It is attributed to the compact intermolecular stacking; the nonradiative consumption of A2‐D1 is suppressed substantially by the restricted intermolecular rotation (RIR) effect. Therefore, A2‐D1 with low PLQY can exhibit an aggregation‐induced emission (AIE) phenomenon in neat films. This work may benefit the rational design of nondoped OLEDs. Abstract : The reason for distinctly diverse photoluminescence quantum yield (PLQY) and inverse solid‐state luminescent properties in structure‐similar two diphenyl sulfone thermally activated delayed fluorescence (TADF) molecules is explored in the gas state and solid state.